Study on pore characteristics of cold-mixed multi-component reactive asphalt mixture based on mercury intrusion test - Chong Zhan; Shuyin Wu; Bingshen Chen; Zhexu Wang; Tao Hu; Jun Yang (Case Studies in Construction Materials)
Long term service of cement concrete pavement panels in civil airports often leads in surface degradation and other diseases caused by freeze-thaw cycles. However, conventional overlay repair materials typically exhibit insufficient low-temperature toughness. To address this issue, this study proposes a cold-mixed multi-component reactive asphalt material. Mercury intrusion porosimetry (MIP) was employed to characterize the pore structure of two cold-mixed multi-component reactive asphalt mixtures with varying polyester fiber contents. The results reveal a significant increase in pores ranging from 5000 to 30,000 nm after freeze-thaw cycling. The incorporation of polyester fibers enhances the water stability of the mixture. Furthermore, macroscopic freeze-thaw splitting tests confirm the superior freeze-thaw resistance of polyester fiber-modified cold-mixed multi-component reactive asphalt mixtures.